IN SILICO ANALYSIS OF ACTIVE CONSTITUENTS OF SILYMARIN AS ΑLPHA-GLUCOSIDASE ENZYME INHIBITORS IN TYPE 2 DIABETES MELLITUS - AHMAD ZONOUBI; PRASHANTHA CN; D VISAGA PERUMAL; ZAHRA MAFIBANIASADI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Type 2 diabetes mellitus (T2DM) is an acute metabolic disorder, in which the vogue is increasing persistently globally. The maltase-glucoamylase/alpha-glucosidase inhibitor is an oral antidiabetic drug collectively, which is utilizing for regulating carbohydrates that ordinarily transformed into simple sugars and absorbed by the intestine. Researchers need to constantly explore alternative therapeutic strategies for the clinical management of DM due to the increased adverse event caused by conservative antidiabetic agents. The present study proposes a substitute drug to examine the seven bioactive phytocomponents of Silybum marianum (milk thistle) that can regulate the hyperglycemia by downregulating alpha-glucosidase and its activity. Methods: Different integrated web-based in silico tools and techniques were used to model the enzyme (receptor) as well as to determine the druggability of different active constituents of silymarin and their pharmacokinetics were predicted. Further, the active site of the enzyme was predicted followed by molecular docking method. Results: The results show silychristin A and silydianin having less carcinogenicity and strong interaction to the target protein (alpha-glucosidase) compare to the reference drugs (acarbose and miglitol) and these two molecules can be used for the best drug molecules in T2DM. Conclusion: In the proposed study, the in silico analysis helps researchers to utilize these compounds for clinical applications. The conclusion also suggests that synthetically and semi-synthetically, nucleus and peripheral modifications, either in the form of skeletal rearrangements or partial degradations as well as functional group addition and replacement of the active molecules present in silymarin giving access to new structural motifs, which can be used in future as a lead compounds for antagonising the alpha-glucosidase in the treatment of diabetes mellitus.